Preoperative localization of sentinel lymph node in breast cancer patients by silver wire insertion or liquid charcoal injection guided by CT lymphography. Issue 4 (25th August 2019) - Hamdy, Omar; El‐Badrawy, Adel; Saleh, Gehad A.; Metwally, Islam H.; Abdelwahab, Khaled; Farouk, Omar; Denewer, Adel; Setit, Ahmed
Abstract: Dual localization of SLN in breast cancer patients using isotope & dye is the best‐approved modality with limitations such as high cost of radioactive materials, complex logistic preparations & scheduling issues, especially in developing countries. We investigated the feasibility & accuracy of a novel technique for SLN localization using silver wire insertion or liquid charcoal injection guided by CT lymphography. 120 patients with clinically node‐negative breast cancer were enrolled. In the test group, SLN was localized using preoperative CTLG guided injection of liquid charcoal or by placing a 3 cm silver wire. In addition, intraoperative SLN mapping was performed using methylene blue dye followed by searching for the SLN localized by both methods. In the control group, SLN was localized by the blue dye only. Feasibility, accuracy, detection rates, and number of SLNs retrieved were reported as well as matching between the LN detected with the CTLG and that detected with the dye technique. SLN could be detected in 59 out of 60 patients (98.3%) in the test group and in 54 out of 60 patients (90%) in the control group ( P = .057). In self‐controlled analysis of the test group comparing CTLG only to dye only was significant ( P = .050). Comparing charcoal to silver wire in detection was statistically insignificant ( P = .5). This novel method can offer advantages which are as follows: being more accurate than the dye alone, saving operative time, abandoning complex logistic preparations for the radioisotope, and solving the problem of timing.